Stagecraft fundamentals : a guide and reference for theatrical production - Carver, Rita Kogler (Routledge, 2023)
"Stagecraft Fundamentals Fourth Edition is an entry level how-to guide and reference on backstage theatre, covering every aspect of basic theatre production. The history of stagecraft, safety precautions, lighting, costumes, scenery, special effects, career planning tips, and more are discussed, illustrated by beautiful full-color images that display step-by-step procedures. This fourth edition improves upon the last, featuring a new chapter on Costume Crafts, which includes information on millinery, shoes, fabric dyeing, fabric modification, distressing, masks, armor, body padding, and accessories. Also included is expanded discussion on sound, props, rigging, safety, production management, and projection design, new information on digital theatre, new end of chapter exercises, additional information on US/UK standards, and an emphasis on diversity and inclusion. Each chapter features exercises, discussion questions, and study words to help the teacher and student review the content before moving on to the next topic. Stagecraft Fundamentals Fourth Edition is the must-have introductory theatre production book for Stagecraft, Technical Theatre, and Theatre Production courses. A companion website (www.StagecraftFundamentals.com) features additional articles and information, downloadable images and paperwork, chapter quizzes, and an instructor's manual"--